Modified technique for aortic cross‐clamping during liver donor procurement. (19th April 2014) - Desai, Chirag S.; Girlanda, Raffaele; Hawksworth, Jason; Fishbein, Thomas M.
Abstract Undue tension on the donor vessels during organ procurement is associated with intimal dissection, which can form the nidus for the thrombosis of the hepatic artery (HA) and graft loss. According to the US OPTN database, 143 grafts were discarded in the last 15 yr due to vascular damage during procurement. The most common technique to expose the supraceliac aorta is dissection between the left lateral segment of the liver and the esophagus–stomach. In obese donors, due to restricted space and in pediatric donors where the vessels are very delicate and this space is very small, the replaced or accessory left HA(R/A LHA) is prone to damage if approached conventionally. We describe a technique for the exposure of the supraceliac aorta in which the aorta is approached from the left side behind the gastroesophageal junction that does not require division of the gastrohepatic ligament. From May 2007 to May 2013, 104 liver procurements were performed. Eighty‐nine (85.6%) were adults, and 15 (14.4%) were pediatric donors. Twenty‐three (22.1%) had R/A LHA. No donor organ suffered any damage. One adult recipient with R/A LHA suffered HA thrombosis not related to it. In summary, this technical modification offers improved safety during cadaveric procurement and increases the ease.